The Role of Treatment Supporters in Addressing Adverse Effects of Anti-Tubercolusis Treatment: Cross-Sectional Study in Timor Leste - Nita Yunianti Ratnasari; Weni Hastuti; Domingos Soares; Joaquim Gregorio de Carvalho; Jose Dionisio Ximenes; Eduardo C. Gaio (Jurnal Kesehatan Masyarakat, 2026)
Tuberculosis (TB) remains a critical health challenge in Timor-Leste, as one of the 30 countries with the highest TB burden globally. The involvement of Treatment Supporters or Pengawas Minum Obat (PMO) has been widely implemented to address these challenges. Purpose: This study aims to examine the relationship between the presence of active PMO and the incidence of OAT adverse effects among TB patients in Timor Leste. Methods: A descriptive-correlational study was conducted from July to November 2023. A total of 69 pulmonary TB patients who had completed the intensive treatment phase were selected through purposive sampling. Data were collected using a validated questionnaire; analysis was conducted using a chi-square test via SPSS version 26. Results: Among 69 respondents, 10 (14.5%) reported adverse effects, while 59 (85.5%) did not. The most common symptoms included reddish urine (97.1%), loss of appetite (91.3%), and joint pain (34.8%). A significant correlation was found between active PMO presence and absence of reported adverse effects (p < 0.001). Conclusion: The presence of active PMO significantly influences the perception and reporting of OAT adverse effects among TB patients. Strengthening the training and involvement of PMO in TB programs can enhance patient adherence and improve treatment outcomes.